2014
DOI: 10.1016/j.str.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phe187 as a Crucial Dimerization Determinant Facilitates Crystallization of a Monomeric Retroviral Integrase Core Domain

Abstract: Retroviral DNA integration into the host genome is mediated by nucleoprotein assemblies containing tetramers of viral integrase (IN). Whereas the fully active form of IN comprises a dimer of dimers, the molecular basis of IN multimerization has not been fully characterized. IN has consistently been crystallized in an analogous dimeric form in all crystallographic structures and experimental evidence as to the level of similarity between IN monomeric and dimeric conformations is missing because of the lack of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…NTD bridging of the two protomers, within the canonical dimer, can potentially stabilize IN dimers during multimer assembly and reorganization upon DNA binding. We previously proposed that the hydrophobic core at the C-terminal tip of CCD α-5 (around F185 of HIV-1) is delicately tuned for optimal flexibility hinging the two protomers together during IN rearrangements, and a single Phe to Lys mutation at this hinge rendered IN of feline-lentivirus (FIV) monomeric (Galilee and Alian, 2014). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…NTD bridging of the two protomers, within the canonical dimer, can potentially stabilize IN dimers during multimer assembly and reorganization upon DNA binding. We previously proposed that the hydrophobic core at the C-terminal tip of CCD α-5 (around F185 of HIV-1) is delicately tuned for optimal flexibility hinging the two protomers together during IN rearrangements, and a single Phe to Lys mutation at this hinge rendered IN of feline-lentivirus (FIV) monomeric (Galilee and Alian, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…We exploited the distinct multimerization features, tetrameric for HIV-1 IN and dimeric for the FIV IN (Galilee and Alian, 2014), to assess the effects of domain swapping on IN multimerization using size exclusion chromatography. Swapping CTD (H-H-F, CTD of FIV), NTD (F-H-H, NTD of FIV) or both domains (F-H-F, NTD and CTD of FIV) rendered HIV-1 IN chimeras dimeric, an intrinsic feature of the FIV IN (Galilee and Alian, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These intrinsic species-specific pathway preferences, which apparently hinge on variations as subtle as singleresidue mutations, emphasize the power of cross-species analysis in highlighting potentially accessible alternative routes awaiting HIV-1 exploitation. We have recently shown that recombinant FIV integrase (IN), unlike HIV-1, lacks in vitro integration activity and that a single residue mutation in the typically dimeric FIV integrase results in monomerization (25). Further characterization of these distinctions may highlight additional critical requirements for integration in FIV or bring to light divergent cellular routes accessible to monomeric integrase.…”
Section: Flexible Cofactor Targeting Within Crucial Cellular Pathwaysmentioning
confidence: 99%